Men's Knowledge and Attitudes Regarding Vasectomy: A Comprehensive Cross-Sectional Study - Abdelgader, Alla; Elrasheed, Fath Elrahman; Suliman, Hajar; Abuobida, Baharelden; Abdelmageed, Maha Murtada; Elhawari, Sahar; Elzein, Azza Mustafa; Abdelwahid, Awadalla; Alatawi, Zinab; Mohamed, Mohannad (Journal of Neonatal Surgery, 2025)
Background Male sterilization in sub-Saharan Africa, including Sudan, remains underutilized for various reasons, despite its numerous advantages over other family planning methods. Purpose This study aims to assess men's knowledge and attitudes towards vasectomy, identify their sources of information, and evaluate the utilization rate at Omdurman Maternity Hospital in Sudan. Methodology We conducted a quantitative, descriptive cross-sectional study to evaluate the level of knowledge and attitudes toward vasectomy. Data were collected using a structured questionnaire, and a random sampling technique was employed to select 195 respondents for participation. Results The findings revealed that the majority of participants were aged between 28 and 37 years. Notably, 131 respondents (67.2%) demonstrated poor knowledge of vasectomy, despite being familiar with at least one male family planning method. Additionally, 142 respondents (72.8%) expressed a negative attitude towards vasectomy. The study identified a significant association between respondents' education level and their attitudes towards vasectomy (P-value = 0.00), as well as between marital status and attitudes towards vasectomy (P-value = 0.00). Conclusion The study indicates that respondents possess a low level of knowledge regarding vasectomy as a male family planning option and hold negative perceptions about it. These unfavorable views may be influenced by cultural factors, religious beliefs, and a lack of awareness..